A Linguistic Overview of Brand Naming in the Chinese-speaking World - Basciano, Bianca (Annali di Ca’ Foscari: Serie Orientale, 2016)
Brand names are a crucial component of marketing strategies, since they influence brand perception. Chinese consumers seem to be very sensitive to brand names, and thus the choice of an effective brand name is very important for the acceptance of a particular product or service by the public. Generally speaking, there seems to be a tendency towards localization of brand names: foreign brand names undergo adaptation to various degrees in order to meet the needs of the Chinese consumers. A good knowledge of the Chinese language and culture is essential to understand brand naming practices in the Chinese-speaking world and to create suitable Chinese versions of foreign brand names. Here the main linguistic strategies adopted for the creation of Chinese brand names and for the translation of foreign brand names into Chinese are discussed, also highlighting some cultural factors which affect brand naming creation.